2014
DOI: 10.1371/journal.pmed.1001609
|View full text |Cite
|
Sign up to set email alerts
|

Associations between Intimate Partner Violence and Health among Men Who Have Sex with Men: A Systematic Review and Meta-Analysis

Abstract: Ana Maria Buller and colleagues review 19 studies and estimate the associations between the experience and perpetration of intimate partner violence and various health conditions and sexual risk behaviors among men who have sex with men. Please see later in the article for the Editors' Summary

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

18
160
3
7

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 181 publications
(188 citation statements)
references
References 66 publications
(167 reference statements)
18
160
3
7
Order By: Relevance
“…As with other studies in this area, this research involves a convenience sample that is not representative; thus, these results cannot be generalized to the Portuguese population. The instrument uses validated scales for heterosexual samples, which could infl uence factual reporting by same-sex subjects and result in inaccurate measurements of the phenomenon in relationships between people of the same sex (Buller et al, 2014). In this sense, further research is urgently needed, of both a quantitative nature and qualitative nature, on violence in intimate relationships between individuals of the same sex that preferably includes larger and more representative samples of this population, particularly in Portugal.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…As with other studies in this area, this research involves a convenience sample that is not representative; thus, these results cannot be generalized to the Portuguese population. The instrument uses validated scales for heterosexual samples, which could infl uence factual reporting by same-sex subjects and result in inaccurate measurements of the phenomenon in relationships between people of the same sex (Buller et al, 2014). In this sense, further research is urgently needed, of both a quantitative nature and qualitative nature, on violence in intimate relationships between individuals of the same sex that preferably includes larger and more representative samples of this population, particularly in Portugal.…”
Section: Resultsmentioning
confidence: 99%
“…Murray, Mobley, Buford, & Seaman-DeJohn, 2006/2007. In particular, these methodological problems are related to the characteristics of the studies' samples (Buller, Devries, Howard, & Bacchus, 2014;Burke & Follingstad, 1999;Rohrbaugh, 2006;Tjaden & Thoennes, 2000) and the nature of the measure, the type of instruments, and the defi nition of intimate abuse (Buller et al, 2014) used in the studies. Thus, the values found in this study may result from specifi c aspects of the sample itself.…”
Section: Discussionmentioning
confidence: 99%
“…For example, alcohol and illicit drugs could be used so as to cope with abusive relationship dynamics. Previous research has demonstrated that MSM exposed to any form of violence have increased odds of reporting depression-like symptoms (Buller et al, 2014). Similarly, violent relationship dynamics may make it more difficult for MSM to negotiate safer sex practices (e.g., condom use).…”
Section: Discussionmentioning
confidence: 99%
“…A systematic review and meta-analysis among MSM, by Buller et al illustrate a strong association between partner violence and depressive symptoms which in turn leads to poor mental health. The study further concludes that men who are depressed and are part of violent relationship finds it difficult to seek help or to adhere the treatment [15]. The previous studies in different types of populations suggest that physical or sexual violence are associated with poor mental health at an individual level [45][46][47].…”
Section: Discussionmentioning
confidence: 74%